Blood Feuds in Serbia, Montenegro, and Albania Over the Past Two Centuries - Stanimirović, Vojislav; Divac, Una (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
In the Western Balkans, customary law and blood feuds gone hand in hand. The cultute of honour shaped both the practice of blood vengeance and the institution of „umir“ (peace settlement) which was always its opposite. The patriarchal evironment and tribal divisions preserved this phenomenon the longest in Montenegro, Kosovo, and northern Albania. The last two centuries have been marked by intensified efforts to supress it. In Montenegro, the first attemts were made by Vladikas, followed by Prince Danilo, later by the legislation of the Kingdom of Yugoslavia, then by socialist law, and finnally by the new government after the declaration of independence – all aiming to eradicate it. in Kosovo, resistance to any form of authority drove Albanian population to adhere to the Kanun of Lekë Dukagjini. The Ottoman Empire, then Yugoslavia after the Balkan wars and World War I, as well as the socialist regime and subsequent rule under Serbia after the breakup of the SFRY, were largely received with hostility – which deepened the attachement to customary law and intesified animosity toward the non-Albanian population. Yet even the self-proclaimed independence did not eliminate the blood feud- quite a contrary. The tribal life of norhern Albania likewise prevented any governement from replacing custom with positive law, whic today has devastating effects on younger generations. However, over the past hundred years, blood feuds themselves have undergone numerous changes that have distanced them from the original ideals of heroism and honour that supposedly characterized them. In truth, the arbitrary taking of a human life and the trampling of state sovereignty through vigilantism can never be considered an act of heroism or ethics.